KNOW-HOW AS THE SUBJECT MATTER OF A LICENCE AGREEMENT UNDER COMPETITION LAW OF THE EUROPEAN UNION AND THE REPUBLIC OF SERBIA - Vasić, Aleksandra (Zbornik radova Pravnog fakulteta u Nišu, 2025)
This paper analyzes know-how as the subject of a license in the context of competition law of the European Union and the Republic of Serbia. Competition law of European Union thoroughly addresses the block exemption of licensing agreements from the prohibition of restrictive agreements. Know-how, as the subject of a license, must meet clearly defined conditions under the Regulation TTBER in order for such an agreement to benefit from the safe harbour benefits. The main characteristics of know-how are secret, substantial and identified. These characteristics represent three cumulative conditions that must be met for the concerned package of practical information to qualify as know-how under the TTBER. In this paper, author has thoroughly analyzed the key characteristics of know-how from the perspective of EU competition law. On the other hand, Serbian competition law has not yet standardised the institute of block exemption of licensing agreements from the prohibition of restrictive agreements. Block exemption of licensing agreements will be regulated after a regulation on block exemption of technology transfer agreements has been adopted. Namely, the Commission for Protection of Competition prepared the Draft Regulation on technology transfer agreements exempted from prohibition. The aforementioned Regulation should regulate the conditions for exempting technology transfer agreements from prohibition, bearing in mind the mentioned agreements specificities. The proposed solutions in the Draft Regulation referring to know how will be the subject of analysis in this paper.